The association of under-weight and obesity with mortality after hip arthroplasty. (19th September 2018) - Woo, Seung Hee; Cha, Dong Heon; Park, Eun-Cheol; Kim, Seung Ju
Abstract: Background: although many studies have demonstrated the association between body mass index (BMI) and many diseases, there is little evidence of postoperative mortality after hip arthroplasty. The aim of this study was to evaluate the association between BMI and mortality after hip arthroplasty in the older population. Methods: a total of 3, 627 older patients who underwent hip arthroplasty from 2010 to 2013 were included. We used Cox regression analysis to evaluate the association between BMI and mortality after hip arthroplasty. The hazard ratios (HRs) was calculated from 30 days, 31–365 days, and from the first day of surgery to the day of death during the study. Results: under-weight (BMI under 18.5 kg/m 2 ) is significantly associated with increased mortality (HR:1.423; 95% Confidence Interval (CI): 1.023–1.981) after hip arthroplasty compared to the normal range. However, in the short-term mortality within 30 days after surgery, both under-weight (HR: 2.368; 95%CI: 1.130–4.960) and obesity (25–29.9 kg/m 2, HR: 2.023; 95%CI: 1.008–4.059) are associated with increased mortality. Conclusion: our study suggested that under-weight is associated with increased risk of mortality after hip arthroplasty. Further, in a short-term outcome, obesity appear to be associated with increased mortality after hip arthroplasty within 30 days.